PENGARUH EMPLOYEE STOCK OWNERSHIP PLAN, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PERUSAHAAN - Dewi, Ni Wayan Ayu Mutiara; Candradewi, Made Reina (E-Jurnal Manajemen, 2018)
Improving financial performance is one way that companies can do superior to their competitors. To improve financial performance, there are several factors that can affect, including employee stock ownership plan (ESOP), leverage, and company size. This study aims to observe the influence and significance of ESOP, leverage, and firm size on the company's financial performance. This research was conducted at investment sub sector company in Bursa Efek Indonesia in period 2013-2016, which amounted to 11 companies. Sampling is done by using purposive sampling technique. Data collection using nonparticipan observation method. Data analysis method used is multiple regression analysis. The result of the research on F test shows that ESOP, leverage, and company size have significant influence simultaneously or together to variable of company's financial performance. The result of T test shows that partially ESOP, leverage, and firm size have positive and significant influence to company's financial performance